2019
DOI: 10.1002/ijc.32717
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in characteristics and prognoses between Asian and white patients with nonsmall cell lung cancer receiving atezolizumab: An ancillary analysis of the POPLAR and OAK studies

Abstract: This study aimed to compare the differences in characteristics and prognoses between Asian and white patients receiving immunotherapy for nonsmall cell lung cancer (NSCLC). We studied 390 patients who received atezolizumab as part of the POPLAR or OAK trial, and analyzed the differences in baseline characteristics, outcomes and genetic mutations in blood samples between Asian and white patients. Overall survival (OS) was longer in Asian compared to white patients (median OS: 18.7 vs. 11.1 months; p = 0.005). R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 36 publications
10
34
2
Order By: Relevance
“…Besides, Qian et al found that blood-based mutation of GRM3 was associated with response to immunotherapy in NSCLC. 50 Combining these previous findings with our results, we considered that mutations in GRM3 may also play a key promotor in high TMB to increase the potential of response to ICIs in melanoma. However, the mechanism of how GRM3 takes impact on TMB is still unclear at present.…”
Section: Discussionsupporting
confidence: 80%
“…Besides, Qian et al found that blood-based mutation of GRM3 was associated with response to immunotherapy in NSCLC. 50 Combining these previous findings with our results, we considered that mutations in GRM3 may also play a key promotor in high TMB to increase the potential of response to ICIs in melanoma. However, the mechanism of how GRM3 takes impact on TMB is still unclear at present.…”
Section: Discussionsupporting
confidence: 80%
“…An ancillary analysis of individual patient data in the OAK and POPLAR studies suggested that baseline characteristics and genetic mutations may account for the differences of outcome for Asian and non-Asian patients receiving atezolizumab. 40 Ethnic differences in somatic mutations such as STK11, TP53 and EGFR were associated with treatment responses or survival. For example, the mutation rate of STK11 differs among Asian (1.6%) and non-Asian patients (12.3%), which was reported previously to affect efficacy of ICI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed that EPHA5 is frequently mutated in several cancers, including NSCLC [25,42,43]. Mutations in the EPHA5 gene could impair NK cell-mediated cytotoxicity against cancer cells [25] and predict the overall prognosis of cancer patients [44]. In addition to the effects on gene mutations, changes in EPHA5 transcription levels also affect tumor progression (e.g., enhanced drug resistance, invasion and metastatic ability of cancer cells) [45][46][47].…”
Section: Discussionmentioning
confidence: 99%